1994
DOI: 10.1007/bf00006691
|View full text |Cite
|
Sign up to set email alerts
|

Predation risk of typical ovoid and ?winged? morphs of Euplotes (Protozoa, Ciliophora)

Abstract: Freshwater species of the genus Euplotes (Protozoa, Ciliophora) change their morphology in the presence of some of their predators. The ciliates develop extended lateral 'wings' as well as dorsal and ventral projections which make engulfment by predators more difficult. In a series of laboratory experiments ingestion rates of four protozoan predators, the ciliates Lembadion bullinum, Dileptus anser, Stylonychia mytilus and Urostyla grandis, and one metazoan predator, the turbellarian Stenostomum sphagnetorum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…In contrast to behavioral responses, our previous understanding of predator-specific morphological responses has been restricted to studies of aquatic invertebrates. Researchers have found that protozoans (Kuhlmann andHeckmann 1994, Kusch 1995), rotifers (Stemberger and Gilbert 1987), and cladocerans (Dodson 1988, Black 1993) produce different morphological phenotypes in the presence of different predators. Predator-specific changes in morphology have been previously undescribed in larval amphibians; the current study suggests that they may be common.…”
Section: In Contrast Wood Frogs Developed a Deeper Tail Fin In The Pmentioning
confidence: 98%
“…In contrast to behavioral responses, our previous understanding of predator-specific morphological responses has been restricted to studies of aquatic invertebrates. Researchers have found that protozoans (Kuhlmann andHeckmann 1994, Kusch 1995), rotifers (Stemberger and Gilbert 1987), and cladocerans (Dodson 1988, Black 1993) produce different morphological phenotypes in the presence of different predators. Predator-specific changes in morphology have been previously undescribed in larval amphibians; the current study suggests that they may be common.…”
Section: In Contrast Wood Frogs Developed a Deeper Tail Fin In The Pmentioning
confidence: 98%
“…Euplotes respond to the predatory flatworm Stenostomum by producing large lateral wings, a dorsal ridge, ventral projections and significantly increasing their maximum body width (Wiackowski & Staronska, 1999;Altwegg et al, 2004). Such morphological changes lead to a significantly reduced probability of ingestion by predators (Kuhlmann & Heckmann, 1994). Changes in Euplotes behaviour have also been documented following exposure to amoeboid predators, although actual movement rates were not quantified and behavioural and morphological defences were not compared (Kusch, 1993a).…”
Section: Introductionmentioning
confidence: 96%
“…Among these kinds of interactions some ciliates have evolved different defensive strategies to avoid the predation by microturbellarians. An example is given by the inducible defenses where ciliates in the genus Euplotes may show phenotypic and behavioral changes induced by the release of an active kairomone from the predator (Kuhlmann & Heckmann 1985, 1994Kush 1993;Hammil et al 2009). Instead other ciliates are able to release some secondary metabolites (toxins) from peculiar organelles called "extrusomes" to ward off potential predators including microturbellarians (Harumoto et al 1998;Buonanno 2005;Buonanno et al 2005).…”
Section: Introductionmentioning
confidence: 99%